2012
DOI: 10.1100/2012/635169
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical and Immunopathological Features of Different Infective Doses ofTrypanosoma cruziin Dogs during the Acute Phase

Abstract: Infection with Trypanosoma cruzi is a major risk in Latin America, and dogs are believed to be good models for evaluating Chagas disease. Here, we evaluated the clinical and immunopathological alterations developed by mongrel dogs experimentally infected with different infective doses (2,000, 20,000, and 200,000 metacyclic trypomastigotes of Sylvio X10/4 strain kg−1 via intraperitoneal). Clinical and electrocardiographic parameters, as well as antibody production and pathologic lesions were evaluated. All thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
1
6
0
2
Order By: Relevance
“…Mortality in the groups of dogs was not observed throughout the experiment, unlike other studies where experimental T. cruzi inoculation caused sudden death in some of the infected dogs [10,11,17,32,36]; however, some of these authors worked with mongrel dogs and with different number of animal samples, with another T. cruzi strain or morphologic form of the parasite and different amounts of inoculum, or employed different administration routes. Our experimental canine model of CD has already been standardized in accordance with lethal doses 50 assays to determine an adequate inoculum and achieving the establishment of the acute and chronic phases of CD through the systemic infection (one of the natural routes of infection in dogs, besides of the oral route by ingesting the vector).…”
Section: Discussionmentioning
confidence: 81%
“…Mortality in the groups of dogs was not observed throughout the experiment, unlike other studies where experimental T. cruzi inoculation caused sudden death in some of the infected dogs [10,11,17,32,36]; however, some of these authors worked with mongrel dogs and with different number of animal samples, with another T. cruzi strain or morphologic form of the parasite and different amounts of inoculum, or employed different administration routes. Our experimental canine model of CD has already been standardized in accordance with lethal doses 50 assays to determine an adequate inoculum and achieving the establishment of the acute and chronic phases of CD through the systemic infection (one of the natural routes of infection in dogs, besides of the oral route by ingesting the vector).…”
Section: Discussionmentioning
confidence: 81%
“…In another, Andrade et al (1984, p. 94) demonstrated 'high mortality' approximately 3 weeks after infection, with all dogs exhibiting severe myocarditis during the acute phase. More recently, Quijano-Hernández et al (2012) have reported sudden death and mortality rates of 25%-33% (depending on dose) within 36 days of infection. In a second study 50% of unvaccinated dogs died within 5-10 weeks of being infected, with one-third of those vaccinated before infection dying within this time, along with a fifth of those that received a vaccine therapeutically after infection (QuijanoHernández et al 2013).…”
Section: Canine Trypanosomiasismentioning
confidence: 99%
“…2,3 La EC en los perros es clínicamente similar a la de los humanos: la fase aguda puede ser fatal en los animales jóvenes o presentar la fase crónica con cardiopatía y muerte súbita. 4 Algunos estudios realizados en zonas endémicas han demostrado que la EC en los perros tiene una mayor prevalencia que en las personas. 5,6 El presente estudio piloto estuvo enfocado en la detección de anticuerpos contra T. cruzi en el suero de 108 perros que fueron atendidos por diversas razones en 2014 en varias clí-nicas veterinarias del área conurbada de Cuernavaca, Morelos.…”
Section: Evidencia Serológica De Infección Por Trypanosoma Cruzi En Punclassified
“…4 La revisión documental [5][6][7] mostró que la intimidación escolar es un factor de riesgo de la conducta suicida, 8 por lo cual se buscó determinar la presencia y relación entre la intimidación escolar y el intento e ideación suicida en un grupo de jóvenes colombianos. Se utilizó la prueba no paramé-trica U de Mann-Whitney para determinar si la diferencia entre quienes han intentado suicidarse y quiénes no es significativa.…”
Section: ) †unclassified